Passiflora albopurpurea, a new species of sect. Granadillastrum (Passifloraceae, subg. Passiflora) discovered in the central montane forest of Peru - Chávez-Corcuera, Gonzalo; Castañeda, Roxana; Gutierrez, Harol; Ocampo, John (Phytotaxa, 2026)
A new species of Passiflora sect. Granadillastrum belonging to P. subg. Passiflora discovered in the montane forests of Peru is described and illustrated. This new taxon, Passiflora albopurpurea, differs from P. crassifolia by having entire 3–5-nerved leaves, corona in 6 or 7 series, sepals, petals and inner row of corona white and a glabrous ovary. A taxonomic discussion and a distribution map are provided, along with keys for the identification of morphologically related species occurring in Peru. This new species is rare, due to its restricted occurrence with a small population size and should be considered under category Endangered (EN).